The reality of technical and vocational education and training and its suitability for gender requirements from the students' point of view in Salt; Balqa Governorate, Jordan - Al Hamadeen, Hind Mousa (Journal of Educational and Psychological Sciences, 2020)
The study aimed to shed light on the reality of technical and vocational education and training and its suitability for gender requirements from the students' point of view Salt; Balqa Governorate, Jordan, the descriptive analytical method was used through the questionnaire tool, and distributed to a random sample of (234) students In vocational schools, the vocational training center, and Al-Balqa Applied University, the results showed that the majors and programs offered are directed to males at a rate of (82.9%) compared to (17.1) for females, and that the reality of this education from the students ’point of view obtained a total average (3.88 out of 5), i.e. a (large) estimate and In terms of dimensions; the devices and infrastructure got the highest average (4.15), followed by the faculty with an average of (4.04), then after gender and societal view with an average of (3.94) and the fourth dimension is the curricula and study programs with an average of (3.82) and providing job opportunities with an average of (3.81) is the fifth dimension and the last dimension is the directions towards technical education with an average of (3.50), all of which are (large). The results showed that there were no statistically significant differences at the level of significance (α = 0.05) between the sample responses according to the gender variable; whereas differences were found according to a variable according to the variable of the educational institution type (governmental, private) in two dimensions (devices and infrastructure, the teaching staff) and the differences were For the benefit of the special education category, and according to the variable of the type of educational institution (technical college, vocational training center, vocational school) in the two dimensions (devices and infrastructure, faculty) between a technical college and vocational and technical schools for a technical college. And between the vocational training center and vocational and technical schools for the benefit of the vocational training center, in light of the results, a number of recommendations and proposals were presented, the most important of which are: Implementing programs and curricula that are gender-sensitive and gender-appropriate so that they meet the actual needs of labor markets and motivate women to work with them without discrimination, and, in addition to benefiting from developments and trends in developed countries in the world in the field of Technical and vocational education.
Keywords: Training; Technical Training; Vocational Education; Gender; Salt